The Antarctic dive guide - Kelley, Lisa Eareckson (WildGuides., 2015)
The Antarctic Dive Guide is the first and only dive guide to the seventh continent, until recently the exclusive realm of scientific and military divers. Today, however, the icy waters of Antarctica have become the extreme destination for recreational divers wishing to explore beyond the conventional and observe the strange marine life that abounds below the surface. This book is packed with information about the history of diving in Antarctica and its wildlife, and features stunning underwater photography. The Antarctic Dive Guide covers 31 key dive sites on the Antarctic Peninsula and South Georgia.